Wartime Propaganda and Gender in Ahmad Mahmoud’s The Scorched Earth: A Dissident Reading - Farhadi, Ramin (Text Matters: A Journal of Literature, Theory and Culture, 2020)
The Iran-Iraq War (1980–88) has been the subject of many aesthetic productions in contemporary Persian literature. The Iranian mass media during the war with Iraq described the armed conflict as holy and masculine, and propagated the replacement of the word “war” with “sacred defense” to urge authors to write within this established framework and reflect the ideals of the State. Opposed to such an ideological view of the war, the prominent Iranian novelist Ahmad Mahmoud began to express dissent in his works of fiction such as The Scorched Earth (1982). This study, therefore, analyzes Mahmoud’s scope of dissidence toward wartime propaganda and gender in the above mentioned novel to articulate how Mahmoud raises important questions regarding the State’s view of war and the established gender norms in Iran at war. It uses cultural materialist dissident reading and textual analysis to study Mahmoud’s contempt for wartime propaganda through the text’s portrayal of desperate people in Khorramshahr in the southwest of Iran caught between Iraqi airstrikes and artillery fires, and domestic problems including inflation, looting and mismanagement.